Improving The Students’ Writing Skill By Using Clustering Technique - Muhyiddin Aziz; Imam Mudofir; Eda Maaliah; Alief Sutantohadi; Yulius Harry Widodo; Dian Palupi; A’thi Fauzani Wisudawati (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The main aim of the research was to find out the improvement of the students’ writing skill through a clustering technique. This study was a Classroom Action Research (CAR) which was done in three cycles by following the stages of planning, acting, observing, and reflecting. The subjects of the research were 26 students of English Study Program in Madiun State Polytechnic. The data collected were in the forms of qualitative and quantitative. The researchers used quantitative data taken from the scores before implementing a clustering technique (pre-test) and the scores after the implementation (post-test). Besides, quantitatative data were taken from the interview and observation to reveal the improvement after the implementation of a clustering technique. The results showed that the students were interested in writing by using a clustering technique. As a result, most of the students gradually improve their writing skill in composing a paragraph at the end of each cycle. The current study provides an insight for teaching writing for EFL students especially in developing good paragraphs.